A REVIEW OF PHYSICAL AND MECHANICAL PROPERTIES OF CASSAVA RELATED TO HARVESTING MACHINES - ATSYO, Sena Yaw; KORKMAZ, Cem; OZLUOYMAK, Omer Barıs; GUZEL, Emin (MATTER: International Journal of Science and Technology, 2020)
For many years now, harvesting of cassava is difficult because there has not been a well-designed machine to harvest, separate, and convey the crop in a one-time operation. In all the unit operations in cassava production, several machines and types of equipment have been mechanized successfully. However, cassava harvesting and peeling have remained a global challenge to engineers involved in machine design. In light of this, some pieces of literature on the physicomechanical properties of cassava were qualitatively reviewed. The study presents harvesting methods for cassava around the globe, considering its merits and limitations for future development. We found out that cutting shear stress and force increased with increasing cassava tuber age because of an increase in density and starch content. Additionally, the ratio of the peel of cassava tuber ranges from 0.106 to 0.215. The frictional properties of cassava are essential to design and develop machines for post-harvest operations of cassava roots. Whereas, the angle of repose for the unpeeled cassava is required for the design of the hopper and that of the peeled is required for the design of the chute. The manual, semi-manual and fully mechanized harvesting methods require the capacity of about 22-51 man h/ha, 16-45 man h/ha, and 1-4 man h/ha respectively. The fully mechanized method is very efficient, and the field is plowed alongside harvesting which saves time, fuel, and cost of operation. Even though less research is carried out on cassava harvesting mechanization compared to other crops, the current development is a harvesting machine hitched to a tractor with a conveyor unit powered by the PTO system. The knowledge of this review would be a blueprint for engineers in designing cassava mechanical harvesters.